2021
DOI: 10.1016/j.esxm.2020.100302
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of a Comprehensive Sex Education Self-Study Website for Teaching Reproductive Health: A Pilot Study Among College Students and Obstetrics and Gynecology Resident Physicians

Abstract: Introduction: There is a growing interest among adolescents to obtain sexual health information online, which could be helpful in rural areas where adolescents face unique obstacles to contraception access, and medically accurate sex education is not mandated. Aim: This study piloted a comprehensive sex education self-study website among undergraduate students and resident physicians to assess the accuracy and feasibility for future use in younger adolescents. Methods: A sex education website developed by a bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
(17 reference statements)
0
9
0
2
Order By: Relevance
“…The results showed that general practitioners considered the course helpful and were satisfied with the content and layout [ 25 ]. Another pilot study with 10 obstetrician–gynecologist resident physicians and 14 undergraduates assessed the usability of a reproductive health self-study website, comprising four online sessions [ 24 ]. The course was evaluated in terms of medical accuracy, ease of use, and overall usefulness, using the Likert scale, and the results unequivocally showed that the online platform is an acceptable way to learn.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results showed that general practitioners considered the course helpful and were satisfied with the content and layout [ 25 ]. Another pilot study with 10 obstetrician–gynecologist resident physicians and 14 undergraduates assessed the usability of a reproductive health self-study website, comprising four online sessions [ 24 ]. The course was evaluated in terms of medical accuracy, ease of use, and overall usefulness, using the Likert scale, and the results unequivocally showed that the online platform is an acceptable way to learn.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, regarding evaluation, we asked for an individual evaluation for each module, not only in terms of its usability but also completeness, correction, and accuracy. Furthermore, each question of the evaluation questionnaire of the eHealthResp platform (both the online course and the mobile app) had a 5-point Likert scale, which allowed for the feedback to be more precise than, for instance, the Yoost et al study [ 24 ], where some questions only had a 3-point Likert scale, thus providing a less exact feedback.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations